Fully Integrated W-CDMA IF Chip-Set for UMTS Mobiles - Thomann, Wolfgang; Fenk, Josef; Hagelauer, Richard; Weigel, Robert (Radio Frequency Integrated Circuits (RFIC) Symposium, 2001)
A fully integrated Si bipolar IF-receiver and IF-transmitter with on-chip synthesizer for use in third-generation variable duplex W-CDMA mobiles is introduced. Both devices incorporate an IF-synthesizer with on-chip VCO tuning and tank as well as 5th order baseband filters and comply with ARIB W-CDMA and UMTS standards. The devices are mounted in a small outline, 32 pin, leadless surface mount package.
elib2cris::1512001600,thomann2001a